Pedestrian Route Choice Of Vertical Facilities At Kuala Lumpur City Centre Underground Train Station - Tee, Xin Lei (Universiti Sains Malaysia, 2018)
The increasing of ridership of Light Rail Transit (LRT) Kelana Jaya Line must be supported by efficient egress facilities in train station to optimise the pedestrian movement. However, limited route choices to egress platform level via stairways and escalators especially in underground train station are suspected to cause congestion and delay to egress the platform especially during the peak hours. In this dissertation, pedestrian route choice at Kuala Lumpur City Centre underground train station was studied by using Pedestrian Following Survey. The results showed that LRT users at the underground train station preferred to use the vertical facility that is nearer to their respective train doors due to the shortest path, except the passengers that alighted from the middle section of train and tended to egress with escalators over stairways, resulting in the percentage usage of escalators (52.3%) was higher than stairways (47.7%). LRT users at the underground platform walked faster towards stairways by at most 31.5% compared to the escalators. This is because pedestrians tended to use escalators thus reduced speed that caused by the overcrowded at the entrance of escalators. Hence, escalator users experienced higher delay in time by at least 30.1% compared to the stairway users. However, after the users boarded the vertical facilities, those who used stairways experienced higher delay time by at least 48.8% compared to those who used escalators that has uniform escalator operating speed. This dissertation can help the train station operators to have better understanding on pedestrian route choice to egress the underground train station and can be used as a reference for future facility design of underground train station.